Rumah Susun Nelayan dengan Pendekatan Arsitektur Ekologis di Muara Angke Jakarta - Muhammad Bayu Febrianto; Sumaryoto Sumaryoto; Tri Joko Daryanto (Universitas Sebelas Maret Surakarta, 2017)
The high rate of population growth and the lack of land availability in Jakarta, causing some segments of the population do not have the ability to buy a house so they build one in the illegal land. Muara Angke which known as a fisher village has a wide range of environmental problems due to the illegal settlement of which is the problem of garbage and waste. The north coast of Jakarta reclamation project, the government is planning to organize the settlements in the region with flats programs. Based on this phenomenon, namely how the flats are planned to be a friendly place for fishermen activities and will support housing by the application ofprinciples of friendly environtment, efficiency energy and create a friendly building system. Flats with environmental improvement of the standard will provide a better life for the fishermen, it can be achieved by the application of three principles of ecological architecture at the processing site, discovering form and mass, structure and utilities. Concept of The Flat’s Fishermen will support the planning of flats that provide green spaces, energy efficiency at building facade, and waste management to prevent the building for not providing environmental pollution.Keywords: Ecological Architecture, Fishermen, Flat.